BONE ASH INFLUENCE ON SOIL CONSOLIDATION (Malaysian Journal of Civil Engineering, 2018)
Research work on the utilization of bone ash as soil stabilizer revealed that the ash has positive effect on soil strength but no report on it influence on soil settlement. In order for a material to act as stabilizer, its impact on soil settlement characteristics must be investigated. Hence, this research investigated the influence of bone ash stabilizer on the settlement characteristics of soil. Two soil samples were collected from two locations within Ibadan metropolis Nigeria. Bone ash was prepared from calcination of cattle bones at a temperature of 1100Â°C in electric furnace. After grinding, the ash was added to the collected soil samples in varying proportions by dry weight (3%, 5%, 7%, 10%, 15% and 20%) in order to determine the compressibility behaviour of the soil at different proportions of bone ash. The settlement characteristics investigated were compression index, coefficient of consolidation, preconsolidation pressure, coefficient of area and volume compressibility and initial void ratio of both control soils and twenty four stabilized soil samples. The result revealed that Soils A and B coefficient of volume and area compressibility, and compressibility index reached their lowest level at 7 and 10% stabilization which is good for engineering. The soils pre-consolidation pressure and coefficient of consolidation reached peak values at 7 and 10% bone ash stabilization. Therefore, addition of about 7 to 10% of bone ash to the soils will reduce their settlement potential and increase their stability.